SINTESIS DAN KARAKTERISASI KOMPOSIT FIBER SABUT KELAPA SAWIT DENGAN RESIN EPOKSI - Adhi Setiawan (P3M Politeknik Negeri Indramayu, 2020)
The use of natural fiber as reinforcement for epoxy polymer composites is currently a concern for researchers because it is environmentally friendly so it can replace glass fiber or carbon in engineering applications. Palm fiber is a type of natural fiber that is produced by the cooking oil industry as a component of waste. The surface modification of fiber with NaOH solution is one of the factors that determines level of adhesion to the epoxy polymer matrix. This study to analyze the effect of alkali treatment on the morphology and characteristics of fiber. In addition, the effect of palm fiber composition on the mechanical properties of composites were studied. Alkali treatment on fiber was carried out using 10% wt sodium hidroxide solution. The morphology and characteristics palm fiber before and after alkali treatment were analyzed using SEM-EDX, XRD, and FTIR. Tensile tests were carried out on composites with treated fibers and without treatment with sodium hidroxide solution. The results showed that alkali treatment caused the surface morphology of the fiber to be finer due to the loss of lignin and hemicellulose components. Alkali treatment fiber can increase the tensile strenght. Composites with fiber and resin composition of 4%: 96% wt that have undergone alkali treatment have a maximum tensile strength of 21.60 MPa.